Patterns in Plato’s Thought
VIII, 216 p.
Keywords: In his teachings and through his choice of the dialogue-form as a mode of communication, Plato emphasized the communal aspect of intellectual work. The need for having a community work together is nowhere more apparent then when the intellectual task set is that of interpreting the ancient philosophers. Those of us who were fortunate enough to spend some of our years as students at Oxford found that among our most inspiring experiences were the meetings of the Oxford Aristotelian So ciety, as well as the seminars in which B.PhiI. students discussed Plato and Aristotle. Up until the past few years no such group existed on the West Coast. In the fall of 1970 some of us got together to form the West Coast Greek Philosophy Conference, which was within a short time renamed by Prof. T. Rosenmeyer as 'the Aristotelians of the West, Unincorporated'. In our monthly meetings we translate and discuss Greek philosophic texts. For the past two years the group has been working on Aristotle's 'Physics'.